The Pearl, its story, its charm, and its value - Cattelle, Wallis Richard, 1848-1912 (Salt Lake City, UT : Project Gutenberg, 2020)
"The Pearl, its story, its charm, and its value" by Wallis Richard Cattelle is a comprehensive exploration of pearls written in the early 20th century. This work delves into the history, allure, and valuation of pearls, exploring their significance across cultures and their journey from the depths of the ocean to becoming coveted treasures. The text combines historical accounts with practical information on pearl quality and market trends, making it appealing to gem enthusiasts and historians alike. At the start of the book, Cattelle paints a vivid picture of the sea's mysterious beauty and the fascinating world of pearls beneath its surface. He introduces readers to the symbolic relationship between pearls and wealth, emphasizing the allure they have held throughout history, especially among royalty and the wealthy. The opening remarks on the natural origins of pearls set the stage for the detailed examination of their value, craftsmanship, and the intricacies involved in pearl diving and trading that unfolds throughout the subsequent chapters. (This is an automatically generated summary.)
Release date is 2020-11-04
Fay Dunn, Fiona Holmes and the Online Distributed Proofreading Team
Keywords: Pearls